2016
DOI: 10.1080/15563650.2016.1201676
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide-related poison center exposures in children and adolescents aged ≤19 years in Texas, 2000–2013

Abstract: Through characterizing pesticide-related poison center exposures, future interventions can be designed to address groups with higher prevalence of exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Our findings are in agreement with these epidemiological reports. Taking into consideration that pyrethroids were commonly detected in children and adolescents, this raises the concern that pyrethroid exposure may present a serious threat to children's health.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in agreement with these epidemiological reports. Taking into consideration that pyrethroids were commonly detected in children and adolescents, this raises the concern that pyrethroid exposure may present a serious threat to children's health.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, pesticide-related poison center exposures were defined as all calls with a pesticide reported as an exposure, which was defined based on the reported generic Poisiondex codes (a database that contains product information used to group products). The codes used to define pesticide-related exposures had been previously published [ 8 ]. Poison center data included in this study were the frequency of unintentional pesticide-related poison center exposures by caller county, for three American Association of Poison Control Centers (AAPCC) age groupings for children and adolescents (children ≤5 years, children 6-12 years, and adolescents 13-19 years).…”
Section: Methodsmentioning
confidence: 99%
“…Vidi et al (179) reported a significant association between bifenthrin, cypermethrin, deltamethrin, cis-and trans-permethrin and DNA damage in the hair of residentially exposed children in farmer households. An observational study using data from poison control centres reported that the second most common pesticide group by exposure frequency were pyrethroids, and children aged ≤5 years were the group most at risk of exposure (180). Campos et al (181) suggested an association between pyrethroid exposure and mental disorders.…”
Section: Human Exposure To Pyrethroidsmentioning
confidence: 99%